ASSOCIATION OF MTHFR A1298C GENE VARIANT, DNA DAMAGE, AND TOTAL ANTIOXIDANT STATUS WITH THE RISK OF TYPE 2 DIABETES MELLITUS AND ITS COMPLICATIONS - K, Nithya; W, Isabel; T, Angeline; A.s., Priscilla; A.j., Asirvatham (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: We have examined the association of methylenetetrahydrofolate reductase (MTHFR) gene A1298C variant, DNA damage, and total antioxidant status (TAS) in patients with type 2 diabetes mellitus (T2DM) with and without complications and in healthy controls. Methods: A total of 300 subjects including 100 patients with complications, 100 patients without complications, and 100 controls were included. TAS was assessed by ferric reducing ability of plasma assay. DNA damage was analyzed in lymphocytes using the comet assay. Polymerase chain reaction-restriction fragment length polymorphism analysis was performed to study the MTHFR A1298C gene polymorphism among the study subjects. Results: The results revealed that the MTHFR 1298 AC+CC genotypes were associated with increased risk (2 fold) for diabetes and its complications. When the effect of DNA damage was analyzed, significant differences between individuals with mutant and normal genotype among the diabetic patients (with and without complications) was observed (pâ‰¤0.001). In contrary, no significant difference was found between TAS and 1298 genotypes (AA vs. AC+CC) in Type 2 diabetes patients (with and without complications), p=0.338. We also found a significant difference between the genotypes of the MTHFR A1298C and DNA damage, TAS in T2DM patients (with & without complications) when compared to controls, p<0.001. Conclusions: Our findings suggest that the MTHFR A1298C gene polymorphism is considered as a risk factor for the development of diabetes and its complications among south Indians. Therefore, increased DNA damage and decreased TAS along with the occurrence of a mutant genotype in an individual with diabetes may be at an increased risk for the development of chronic complications.